2018
DOI: 10.31632/ijalsr.2018v01i01.005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pharmacists’ Intervention in Improving Patients Knowledge and Attitude Towards Antibiotic Usage in Klinik Kesihatan Seremban, Malaysia

Abstract: Introduction: Antibiotics are an important tool in the battle against infections. Antimicrobial resistance is an increasing problem; hence the appropriate use of antibiotics is significant in the primary healthcare system in Malaysia. Objective: 1) To understand community's knowledge and attitude towards antibiotic use. 2) To determine the effectiveness of pharmacist intervention in proper antibiotic use. Method: A cross-sectional, prospective study with convenient sampling using a pre-validated guided questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The attitude of pharmacists to antibacterial counselling is vital to ascertaining rational drug therapy and improving therapeutic outcome [1,16]. From the present study, majority of the pharmacists' manifested positive attitude to antibacterial counselling.…”
Section: Pharmacists' Attitude Towards Counselling Of Patients On Antmentioning
confidence: 70%
See 2 more Smart Citations
“…The attitude of pharmacists to antibacterial counselling is vital to ascertaining rational drug therapy and improving therapeutic outcome [1,16]. From the present study, majority of the pharmacists' manifested positive attitude to antibacterial counselling.…”
Section: Pharmacists' Attitude Towards Counselling Of Patients On Antmentioning
confidence: 70%
“…Pharmacists especially those involved with counselling of patients on medication use must keep themselves abreast of updates so as to be effective in counselling [26]. Pharmacists should acknowledge their responsibility of patients' counselling and ensure regular updating of knowledge [1]. In the present study, majority of the pharmacists agreed to the need for regular updating of knowledge.…”
Section: Pharmacists' Attitude Towards Counselling Of Patients On Antmentioning
confidence: 77%
See 1 more Smart Citation
“…The employment of focused one-on-one educational intervention may provide additional benefits in addition to a mass awareness campaign. Consistent with local and foreign studies, targeted educational interventions have shown great effectiveness in improving public knowledge, and perception on antibiotic use and resistance [15,[28][29][30]. Pre-intervention, 36% of the respondents were not aware that self-medication behaviour, such as taking leftover antibiotics or purchasing antibiotics without doctor's consultation, accelerates the process of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 89%
“…The SMA is a serious medical problem still receiving updates [13][14][15]. SMA rates have been reported as 24-90% in university students from different regions and countries [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%